(untitled) (Ustozlar uchun, 2024)
Abstract: This article explores the relationship between language, culture, and happiness and how many cultures use their distinctive language expressions to convey and understand happiness. The article sheds light on the variety of emotional experiences that exist across different countries by examining the impact of cultural values, traditions, and social standards on the language used to express happiness. By researching verbal expressions of happiness, this study intends to expand our understanding of the subtle relationships between language and culture, delivering significant insights into the varied ways in which happiness is seen and transmitted around the world.